Calcadista S.A. - Graeff, Clóvis (1995)
The board of directors of a family-owned company that concentrates 35% of the market for the production and distribution of sports and orthopedic footwear for children and young people, thanks to its quality and technology, must decide on an investment proposal aimed at replacing obsolete files, taking into account the profitability of the investment, not its size. Following its policies and considering that the amount of the investment exceeds 5% of its net worth, the company hires an external consulting firm to make the final decision of the board of directors possible by preparing the analytical approach to the investment. This case aims to convey an overview of the activities involved in the evaluation of a specific investment project. The focus is on the importance of sufficient theoretical foundation to solve other problems, which makes it possible to understand that the performance of a company can be intimately linked to an adequate evaluation of its investment projects. This, in turn, implies the importance of the quantitative aspect of the financial analytical process.